Guinea Savanna Structure and Land-use in Northwestern Nigeria. - Ero, Isaac Izogie (Obafemi Awolowo University, 2014)
The Guinea savanna of northwestern Nigeria was characterised using parameters of climate, soil and vegetation. The scale of variability of the attributes measured in the four localities - Yelwa, Mokwa, Borgu and Jebba - was assessed and found in the case of soil and vegetation to be significant on at least a hectare to hectare scale. Density of all species, the most abundant species, size class distribution, and pattern of woody elements were estimated.